Consumer Legal Protection Against Developer Defaults in Binding Agreements for the Sale and Purchase of Flats - Rabiatun Ramadani, Faizzah; Suraji, Suraji; Kharisma, Dona Budi (MAQASIDI: Jurnal Syariah dan Hukum, 2024)
This study discusses consumer legal protection against developer defaults in the binding agreement for the sale and purchase of flats (PPJB). The increase in housing development, especially through the pre-project selling system, often harms consumers due to uncertainty and default from developers. The research method used is a literature study, with a legal approach and a case approach. Analysis was carried out on Decision Number 91/PDT/2018/PT. Jakarta to assess the legal protection provided to consumers. The results of the study show that regulations, including Law Number 11 of 2011 concerning Flats, provide a strong legal basis for consumers to demand their rights. Consistent law enforcement in default cases creates a precedent that strengthens the position of consumers, increases public trust in the legal system, and creates a conducive environment for flats buying and selling transactions.